Metamaterials: Multilayer Graphene:Polycrystalline ITO for Ultralow‐Power Active Control of Polarization‐Insensitive, Metamaterial‐Induced Transparency (Advanced Optical Materials 12/2014). Issue 12 (December 2014) - Lu, Cuicui; Hu, Xiaoyong; Zhang, Fan; Yang, Hong; Gong, Qihuang
<x xml:space="preserve">Abstract</x> Ultralow power and ultrafast all‐optical control of a polarization‐insensitive metamaterial‐induced transparency are realized by X. Y. Hu, Q. H. Gong, and co‐workers on page 1141. They adopt gold nanoprism trimers as meta‐molecules and use a multilayer‐graphene microsheet/polycrystalline ITO composite as a nonlinear medium. This allows the realization of quantum solid chips based on metamaterials, and also a strategy for constructing photonic materials with large nonlinearity and ultrafast response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>